Consumer’s Buying Preference For Electronic Products In India; Online Vs Retail (International Journal of Scientific Research and Management (IJSRM), 2015)
This article brings out the factors which have been more related and stimulated to buy the products through online as well as retail. This study also examines in understanding the different choices to purchase he product in online and retail segment and similarly tries to find out any specific choices to buy lower price and higher price electronic products through the online or retail. Because now days, consumers wants more ease, innovative and variety in their buying scenario for the products and services. This research article has explored the consumer’s buying preference in India for lower & higher price electronic product. Consumer’s buying preference in India for the electronic products are mostly the same for lower and higher price electronic products in retail outlet. This study will focus in identifying the factors which influences the buyer to purchase electronic products through online mode or retail mode. The researcher will use empirical investigation by collecting the data from the respondents and the findings of the research will be analyzed in detail in the following sections. The research findings shows that Indian consumers prefers and interested to buy the lower price electronic products through online where as they prefer to buy the higher price electronic products from retail shops. Now days buying scenario has been changed & developed by the 3rd generation consumers. Similarly both industries have been grown fast by the educated and modern consumers. They are becoming to believe the technology acceptance model will be the best to decision to have the best service & desired value.